Hypnobirthing Pain Management for Maternal Pain Adaptation along Labor Process - Andriani, Yessi; Primal, Def; Delima, Mera (JOSING: Journal of Nursing and Health, 2020)
The purpose of this study was to determine the effect of hypnobirthing pain management on the adaptability of maternal pain spontaneously. This study uses a quantitative approach to the design quasi-experimental design with treatment replications ( pretest posttest with control group. Research results showed the existence difference in pain adaptation in mothers who are given hypnobirthing pain management intervention is 1,00 (able to adapt). No differences in pain adaptation in women who were not given pain management interventions hipnobirthing ie -0.62 (not able to adapt). Bivariate results revealed the influence of hypnobirthing pain management on the adaptation ability of maternal pain that gave birth spontaneously (p=0.002). We conclude that there is an influence of hypnobirthing pain management on pain adaptability. It is expected that medical services are able to apply hypnobirthing pain management to maternity mothers, and expected to make standardized services procedures on hypnobirthing management for pain relaxations. Keywords : Hypnobirthing, Pain Adaptation, Pain Management